2012
DOI: 10.1590/s1677-55382012000300010
|View full text |Cite
|
Sign up to set email alerts
|

Androgen receptor CAG polymorphism and the risk of benign prostatic hyperplasia in a Brazilian population

Abstract: ARTIcLe InfO _______________________________________________________________ _____________________

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
0
5
0
1
Order By: Relevance
“…There were several association studies in CAG repeats of AR gene and BPH risk. In Brazilian study, there was no evidence for an association between AR CAG repeat length in BPH risk in a population-based sample (Biolchi et al, 2012). However, Renko et al (2008) reported that there was an association between short AR gene CAG repeat length and a small prostate volume, which confirms a previous finding in the Finnish population.…”
Section: Discussionmentioning
confidence: 90%
“…There were several association studies in CAG repeats of AR gene and BPH risk. In Brazilian study, there was no evidence for an association between AR CAG repeat length in BPH risk in a population-based sample (Biolchi et al, 2012). However, Renko et al (2008) reported that there was an association between short AR gene CAG repeat length and a small prostate volume, which confirms a previous finding in the Finnish population.…”
Section: Discussionmentioning
confidence: 90%
“…There are a considerable studies have been conducted to investigate the association between CAG and or GGC repeats located in Xq11.2, and incidence of BPH and PrCa (Alptekin et al, 2012;Biolchi et al, 2012;Cunningham et al, 2007;Giovannucci et al, 1997;Gsur et al, 2002;Gu et al, 2012;Gudmundsson et al, 2008;Lee et al, 2016;Neto et al, 2008;D. Riley and Krieger, 2001).…”
Section: Identification Of Potential Genes For Benign Prostatic Hyperplasia and Prostate Cancer Susceptibility In Four X-chromosome Regiomentioning
confidence: 99%
“…Prostat kanserine benzer olarak farklı popülasyonlarda farklı sonuçlar elde edildi. Japonya ve ABD'de yapılan çalışmalarda AR genin kısa CAG tekrar uzunluğu ile prostat büyüklüğü arasında anlamlı ilişki tespit edilirken (13,14), Hindistan ve Brezilya'da yapılan çalışmalarda ise bu anlamlı ilişki tespit edilemedi (15,16).…”
Section: Androjen Reseptör Gen Polimorfizmiunclassified